Type 2 diabetes mellitus in the Czech Republic: Prevalence and association with individual costs - Petra Kucova; Jana Votapkova (Charles University in Prague, Institute of Economic Studies (IES), 2017)
The paper examines prevalence of type 2 diabetes mellitus in the Czech Republic based on drug consumption. Data for the whole Czech population for the period 2013-2015 was used to identify patients with diabetes and their health care costs. Association between the presence of diabetes and increased individual health care costs was analyzed: findings from a descriptive analysis (Histograms, Pearson's chi-squared test) were supported parametrically (GLM) for the cohort 55-59 which best allows to separate increased marginal costs incurred by patients suffering from diabetes. Besides, the results suggest that up to one third of diabetic patients in the Czech Republic consume low levels of oral antidiabetics which indicate patient nonadherence to recommended therapy or physician nonadherence to current clinical guidelines.
Keywords: I11; I18; 330; Type 2 diabetes mellitus; health care costs; histograms; GLM